Development of an In-Field Real-Time LAMP Assay for Rapid Detection of Tomato Leaf Curl New Delhi Virus - Andrea Giovanni Caruso; Arianna Ragona; Sofia Bertacca; Mauricio Alejandro Marin Montoya; Stefano Panno; Salvatore Davino (Plants, 2023)
Tomato leaf curl New Delhi virus (ToLCNDV) represents a threat to economically important horticultural crops. A real-time loop-mediated isothermal amplification (LAMP) assay for in-field ToLCNDV detection was developed, coupled to a rapid sample preparation method, and tested both in field and laboratory conditions on zucchini squash, tomato, and pepper samples. A set of six LAMP primers was designed for specific ToCLNDV detection, targeting a 218-nucleotide sequence within the AV1 gene. The sensitivity, specificity and accuracy of the real-time LAMP assay and comparison with canonical PCR were evaluated. The real-time LAMP assay developed was about one-thousand times more sensitive than the conventional PCR method, detecting a total of 4.41 × 102 genome copies as minimum target; no cross-reactivity was detected with the other geminiviruses used as the outgroup. The rapid sample preparation method allows for a reliable detection with a low reaction delay (≈2–3 min) compared to canonical DNA extraction, providing results in less than 45 min. Lastly, an increase in ToLCNDV-positive sample detection was observed compared to PCR, in particular for asymptomatic plants (85% and 71.6%, respectively). The real-time LAMP assay developed is a rapid, simple, specific, and sensitive technique for ToLCNDV detection, and it can be adopted as a routine test, for both in-field and laboratory conditions.